A Primer on Needs Assessment: More Than 40 Years of Research and Practice. Issue 144 (December 2014) - Altschuld, James W.; Watkins, Ryan
Abstract: This chapter consists of an overview of needs assessment's rich history, definitions, models, tools, and techniques. These closely align its theory, research, and practice to several associated fields—most notably strategic planning and evaluation. The highlights of the content include a comparison to—and differentiation from—evaluation, a brief timeline of the recent history of the field, the notable emergence of hybrid assessment and asset/capacity building approaches, some discussion of opposition to needs assessment, and a description of two prominent models that guide what assessors do. The summary captures the dynamic nature of the enterprise and how it is evolving.